2010
DOI: 10.1519/jsc.0b013e3181d82e70
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Swiss-Ball Core Strength Training on Strength, Endurance, Flexibility, and Balance in Sedentary Women

Abstract: The purpose of this study was to investigate the effects of Swiss-ball core strength training on trunk extensor (abdominal)/flexor (lower back) and lower limb extensor (quadriceps)/flexor (hamstring) muscular strength, abdominal, lower back and leg endurance, flexibility and dynamic balance in sedentary women (n = 21; age = 34 ± 8.09; height = 1.63 ± 6.91 cm; weight = 64 ± 8.69 kg) trained for 45 minutes, 3 d·wk-1 for 12 weeks. Results of multivariate analysis revealed significant difference (p ≤ 0.05) between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 26 publications
7
80
1
11
Order By: Relevance
“…Improvements in balance have been reported in various populations following a 6e8 week training program incorporating the Swiss Ball (Sekendiz et al, 2010), uniaxial or multiaxial unstable surfaces (Eisen et al, 2010), resistance training incorporating unstable surfaces (Sparkes and Behm, 2010;Schilling et al, 2009), core stability (Aggarwal et al, 2010) and progressive neuromuscular training (Filipa et al, 2010). The present results extend the past literature demonstrating the ability of a short, four-week targeted training program to increase balance in middle aged women (as documented by reduced positional errors during the BESS) through the manipulation of training variables that included base of support, stability, vision, resistance and torque.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in balance have been reported in various populations following a 6e8 week training program incorporating the Swiss Ball (Sekendiz et al, 2010), uniaxial or multiaxial unstable surfaces (Eisen et al, 2010), resistance training incorporating unstable surfaces (Sparkes and Behm, 2010;Schilling et al, 2009), core stability (Aggarwal et al, 2010) and progressive neuromuscular training (Filipa et al, 2010). The present results extend the past literature demonstrating the ability of a short, four-week targeted training program to increase balance in middle aged women (as documented by reduced positional errors during the BESS) through the manipulation of training variables that included base of support, stability, vision, resistance and torque.…”
Section: Discussionmentioning
confidence: 99%
“…Core training actually contributes to enhanced strength in athletes (Segal et al, 2004; Sekendiz et al, 2010). Core stability enables stabilization of the body during movement, which is a crucial prerequisite to muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…Despite minor improvements in case 1's Biering Sorensen results, Previous studies have demonstrated improvements in the Biering Sorensen of 56.9 secs at one year follow up with 'functional restoration' training incorporating aerobic and resistance exercise for 5 weeks in back pain patients [13]. Few studies have followed trunk muscle endurance over an entire year, however studies of shorter durations have found increases in the Biering Sorensen ranging from 30.34% to 46.95% [14,15]. The improvements in trunk endurance are important as a lack of endurance has been found to be a major reason for the recurrence and chronicity of low back pain [16].…”
Section: Casementioning
confidence: 99%